Efficacy of hyperbaric oxygen therapy in patients with radiation‐induced rectal ulcers: Report of five cases. Issue 6 (24th April 2017) - Yoshimizu, Shoichi; Chino, Akiko; Miyamoto, Yuji; Tagao, Fuyuki; Iwasaki, Susumu; Ide, Daisuke; Tamegai, Yoshiro; Igarashi, Masahiro; Saito, Shoichi; Fujisaki, Junko
Abstract : For decades, hyperbaric oxygen therapy has been considered a treatment option in patients with chronic radiation‐induced proctitis after pelvic radiation therapy. Refractory cases of chronic radiation‐induced proctitis include ulceration, stenosis, and intestinal fistulas with perforation. Appropriate treatment needs to be given. In the present study, we assessed the efficacy of hyperbaric oxygen therapy in five patients with radiation‐induced rectal ulcers. Significant improvement and complete ulcer resolution were observed in all treated patients; no side‐effects were reported. Hyperbaric oxygen therapy has a low toxicity profile and appears to be highly effective in patients with radiation‐induced rectal ulcers. However, hyperbaric oxygen therapy alone failed to improve telangiectasia and easy bleeding in four of the five patients; these patients were further treated with argon plasma coagulation (APC). Although hyperbaric oxygen therapy may be effective in healing patients with ulcers, it seems inadequate in cases with easy bleeding. Altogether, these data suggest that combination therapy with hyperbaric oxygen therapy and APC may be an effective and safe treatment strategy in patients with radiation‐induced rectal ulcers.